Design and Build a Motor Vehicle Information System App using Location Based Service in the City of Malang - Abror, Muhammad; Aisah, Aisah; Atmadja, Martono Dwi (Jurnal Jaringan Telekomunikasi, 2023)
The service queue system at motor vehicle repair shops in Malang city is still manual, customers must find the nearest repair shop and visit the repair shop then queue for service without knowing the queue information. With a system like that, it will be difficult and take a long time for customers who want to do service. For this reason, we need an application to search for the nearest motor vehicle repair shop based on maps based on LBS (Location Based Service) and a motor vehicle service queue information system using a web server and applications with the Android operating system. The application of the location-based service concept to the workshop queuing information system application can be used to provide location-based information services. Customers will use an application that displays workshop information and the number of service queues according to what is input by the workshop admin. The result of this research is workshop queue information system application can be used to find out the user's location and the location of the nearest special vehicle repair shop around the user. From the experimental results, it is found that the web and application can work well.